Finite-Time Fault-Tolerant Control for a Robotic Manipulator With Output Constraint and Uncertainties - Duc Thien Tran (IEEE, 2021)
This paper proposed a finite-time backstepping control for a robotic manipulator under the presence of actuator fault, saturation constraints, output constraints, and external disturbance to obtain requirements about the robustness, fast convergence, and high accuracy tracking performance. To manage the above challenges, the proposed control is designed on a transformed model with the backstepping approach and extended state observer. The transformed model is resulted from converting a constrained system based on a transformation technique. So, it provides an ability for the proposed control to obtain the prescribed performance of the output response. Additionally, an extended state observer is conducted to deal with the lumped uncertainties in the system. The essential characteristic of the proposed control is no required knowledge of the actuator faults and external disturbance to be available. Furthermore, fractional-order terms are added in the control laws to enhance the rate of output responses. To demonstrate the advantages of the proposed control in terms of global asymptotic stability, the Lyapunov approach is used to verify the whole controlled system in theory. The proposed control is applied to a 2-degree of freedom (DOF) manipulator and simulated by MATLAB Simulink. Its simulation results are compared to other state-of-the-art methods to exhibit the effectiveness of the proposed control.